Ответы и объяснения

2012-05-23T00:57:56+04:00

1)√(3-2x)=6+x;

Возводим в квадрат левую и правую часть уравнения:

(√(3-2x))²=(6+x)²;

3-2x=36+12x+х²;

36-3+12x+2x+х²=0;

х²+14х+33=0;

По теореме Виета: х₁=-3, х₂=-11.

Проверка:1)х₁=3, √(3-2·(-3))=6-3; 3=3(верно0

2) х₂=-11, √(3-2·(-11))=6-11; 5=-5 (не верно)

Ответ: х=3.

2). 3^(x+1)+2*3^(x+2)=21;

 3·3^(x)+2·3²·3^(x)=21;

3^(x)·(3+18)=21;

3^(x)=1;

3^(x)=3⁰;

х=0.

3)log₄(x^(2)+2x+49)=3;

по определению логарифма:

х²+2х+49=4³;

х²+2х+49-64=0;

х²+2х-15=0;

по т.Виета: х₁=3, х₂=-5.

Проверка: 1)х₁=3, log₄(3²+2·3+49)=3; log₄64=3, 4³=64(верно);

2)х₂=-5, log₄((-5)²+2·(-5)+49)=3; log₄64=3, 4³=64(верно).

Ответ:х₁=3, х₂=-5.